Pengabdian Masyarakat Dasar-dasar Komunikasi dan Public Speaking di SMK Lab School of Uhamka, Cariu Kabupaten Bogor - Ade Sarengat Pakanheran (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Public speaking skills training for students at Vocational School Lab School of Uhamka, Cariu, Bogor Regency. Community Service (PKM) is an effort by the community service team to provide knowledge and technology to the community and especially in Community Service with students. Based on this, the team submitted a proposal for PkM activities at the Vocational Lab School of Uhamka, Cariu in Bogor Regency. The aim of Community Service (PKM) is designed to provide insight and practical skills to students at the Vocational School Lab School of Uhamka Cariu, Bogor regarding readiness to speak in public, namely the basics of communication and Public Speaking. This training is expected to motivate and provide students with the benefits of practicing speaking in public and is also beneficial for developing students' knowledge and solving problems related to speaking errors. The benefit of this activity is that training participants can improve their skills and courage in communicate, reduce anxiety and fear in making presentations independently, increase self-confidence and motivate student learning